Studi Kinerja Silinder Berpori Dalam Mereduksi Genangan Terhadap Struktur Tanah Pada Saluran Drainase: - Mahendra, Yusril; Nenny; Antaria, Sukma Sari; Aditya, Muh. Mufti (Jurnal Karajata Engineering, 2025)
Flooding is often a problem on urban roads, especially during the rainy season. Floods are caused by a variety of things, including high rainfall, or inadequate drainage systems. especially in the Tamarunang Housing area in Gowa Regency where poor infrastructure and inadequate drainage systems can cause flooding and waterlogging. The purpose of this study is to conduct soil analysis on the influence of soil structure on the performance of porous cylinders, the influence of soil structure on the infiltration process, and to determine the infiltration discharge capacity of soil structure in drainage channels. The research was conducted in a residential area located in Gowa Asri, Tamarunang, Somba Opu District, Gowa Regency. With a total area of 6,661m2 located between 5°12'38'' South and 119°28'17'' E. This study uses a quantitative method, with the average permeability result produced per day is 3,119 mm3/day.